2010
DOI: 10.1614/wt-09-009.1
|View full text |Cite
|
Sign up to set email alerts
|

Environment and Soil Conditions Influence Pre- and Postemergence Herbicide Efficacy in Soybean

Abstract: Deciding on the most efficacious PRE and POST herbicide options and their ideal application timing can be challenging for soybean producers. Climatic events during the 14 d before and after herbicide application can further complicate decisions because of their influence on herbicide effectiveness. Nine field trials were conducted at three locations in southwestern Ontario from 2003 to 2006, to determine the most effective PRE and POST soybean herbicides for control of common lambsquarters, common ragweed, gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 34 publications
(44 reference statements)
0
39
1
1
Order By: Relevance
“…This wide range of time to control weeds to avoid yield losses necessitate glyphosate applications timings that are specific to weed populations and environmental conditions where glyphosate resistant cropping systems are being used [12]. Research has shown that a single-pass herbicide program with no residual activity can result in late emerging weeds and result in yield losses [13][14][15][16][17][18]. Other research has shown that it is possible to eliminate any yield loss due to weed interference with a single properly timed glyphosate application in glyphosate-resistant corn [19].…”
Section: Introductionmentioning
confidence: 99%
“…This wide range of time to control weeds to avoid yield losses necessitate glyphosate applications timings that are specific to weed populations and environmental conditions where glyphosate resistant cropping systems are being used [12]. Research has shown that a single-pass herbicide program with no residual activity can result in late emerging weeds and result in yield losses [13][14][15][16][17][18]. Other research has shown that it is possible to eliminate any yield loss due to weed interference with a single properly timed glyphosate application in glyphosate-resistant corn [19].…”
Section: Introductionmentioning
confidence: 99%
“…During 2011, the difference between PRE and EPOST application terms for this herbicide was significant (77% and 100%, respectively, probably due to low total precipitation at the time of sowing (Table 1). According to Stewart et al (2010), cumulative precipitation during the 12 days after PRE application of metribuzin that exceeded the monthly average by at least 60%, reduced C. album control. Mercurialis annua was the most tolerant weed tested; it was significantly better controlled after EPOST herbicide application (73%) compared to PRE application (32%).…”
Section: Resultsmentioning
confidence: 99%
“…Also florasulam controlled all tested sunflower cultivars (efficacy above 85%), except for 2011 when efficacy on ExpressSun was 75% (Tables 4 and 5). Lower herbicide efficacy under dry conditions is usually caused by strongly developed protection structure (such as wax and trichomes) on leaves surface (Stewart et al 2010, Jursík et al 2011.…”
Section: Resultsmentioning
confidence: 99%